Development of E-Worksheets Based on GeoGebra with Jonegoroan Batik as the Learning Context - Alvinna Mei Yunia Putri; Ade Rista Arieyani; Annies Hanifa Rahma; Nonik Indrawatiningsih (Mathematics Education Journal, 2026)
The integration of digital technology and local cultural contexts in mathematics learning has garnered increasing attention, as there is evidence that it can enhance students’ conceptual understanding. However, GeoGebra-based learning with ethnomathematical contexts limited attention in the teaching of geometric transformations. The present study aims to develop GeoGebra-based e-worksheets integrated with the ethnomathematical context of Jonegoroan batik to support students’ understanding of translation concepts. The study employed the ADDIE development model, consisting of the following stages: analysis, design, development, implementation, and evaluation. The e-worksheets developed for this study were validated by two experts in the fields of mathematics education and learning media. The validation results showed a mean score of 3.3 on a four-point scale, indicating the validity. The practicality test, conducted with 38 ninth-grade students from a public junior high school in Pasuruan Regency, yielded a practicality score of 87%, which was categorized as very practical. The effectiveness of the e-worksheets was evaluated using pre-test and post-test results, which were subjected to a Wilcoxon signed-rank test. The effectiveness test using the Wilcoxon signed-rank test showed a significant improvement in students' learning outcomes (Z = –3.421, p = 0.001, r = 0.55), indicating a large effect of the developed e-worksheet. The findings of this study indicate that the developed e-worksheets are valid, practical, and effective for supporting students’ understanding of translation concepts. Additionally, the integration of Jonegoroan batik patterns as an ethnomathematical context within GeoGebra activities helps students connect mathematical concepts with local cultural representations.